Analisis Pengaruh Nozzle Temperature dan Wall Thickness pada Proses FDM Terhadap Kekuatan Mekanik Filamen PETG - Luthfi Maulana A; Zaldy Sirwansyah Suzen; Pristiansyah Pristiansyah (Jurnal Inovasi Teknologi Terapan, 2026)
3D printing has rapidly developed as part of additive manufacturing, with Fused Deposition Modeling (FDM) being widely used due to its low cost and ease of operation. PETG is a popular FDM material because of its good mechanical properties and temperature resistance. However, print quality is strongly influenced by process parameters. This study evaluates the effect of FDM parameters on the impact strength of PETG and determines the optimal settings. The investigated parameters were Nozzle Temperature and Wall Thickness, each tested at three levels. The experiments were designed using the Taguchi method with an L9 orthogonal array, producing nine sample combinations. Specimens were printed using a Haltech H-01 3D printer and tested with the Charpy impact method on a GOTECH GT-7045 machine. Data were analyzed using the Signal-to-Noise Ratio with the “Larger is Better” criterion. Results show that Nozzle Temperature has a more significant effect on impact strength than Wall Thickness, indicated by a higher Delta value and greater variation in mean response. The optimal parameters were a 250°C Nozzle Temperature and 2.5 mm Wall Thickness, providing the best mechanical performance and consistency.